ELECTRICAL IMAGING TECHNIQUES FOR GROUNDWATER POLLUTION STUDIES: A CASE STUDY FROM TAMIL NADU STATE, SOUTH INDIA - K, Srinivasamoorthy; VS, Sarma; M, Vasantavigar; K, Vijayaraghavan; S, Chidambaram; R, Rajivganthi (Earth Sciences Research Journal, 2009)
An attempt was made to identify the extent of pollution in the aquifer matrix of Tirupur, a highly industrialized zone of Tamilnadu state, South India. Electrical imaging techniques were adopted with a Syscal Pro-96 system, for measuring apparent resistivity values using different electrodes separation. The first profile conducted atValipalayam recorded a resistivity range of <10 Ùmat a depth of 8m, which indicates contamination of top soil due to discharge of effluents. An increase in resistivity >45.5 Ùmwas observed at a depth of 27 to 47 mindicating the possibility of contamination. The second profile conducted at Pethichettipuram indicates source of contaminationat left end corner with a drop in resistivity <46.5 Ù m at a depth of 7.91 m. A drop in resistivity <21.6 Ù m was also observed at a depth of 11.5 m indicating a contaminated zone in deeper regolith. The thirdsurvey conducted in Palayakadu indicates contamination of regolith at a depth of 0 to 20 mwith a resistivity less than 40 Ùm. The fourth survey at Chellapuram indicates contamination of overburden with resistivity >11.5 Ùm, to a depth of about 10 m. Five imaging surveys conducted across the contaminated sites reveals that shallower regoliths are highly contaminated and deeper aquifers are free from contamination except a few locations.